Pengembangan Perangkat Pembelajaran Matematika Realistik Terintegrasi ICT untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Ika Dwi Retnowati; Tatag Yuli Eko Siswono; Wiryanto Wiryanto (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
This study aims to develop and obtain valid, practical, and effective realistic mathematics learning tools. The learning tools developed are in the form of lesson plans (RPP), student activity sheets (LKPD), and critical thinking skills tests. The learning device development model used in this study is the four-D from Thiagarajan covering four stages, namely Define, Design, Develop, and Disseminate. However, in this study it was not carried out until implementation so that the result was a final prototype of a learning device that was ready to be implemented. The subjects in this study were 20 fifth grade students at SDN Menur Pumpungan, Surabaya. The results showed that the learning tools developed had high validity, practicality, and effectiveness values. This can be seen from the opinion of the validator, the teacher's response, the student's response, and the results of the field test. Based on the results of field trials, a realistic learning approach can improve students' critical thinking skills better. From these results, it is suggested that learning mathematics in elementary schools uses a realistic mathematics learning approach